Pneumatocele-Induced Pneumothorax in a Patient with Post-COVID-19 Pneumonitis. A Case Report. - Wortman II, Kevin O.; Wortman Sr., Kevin O. (International Journal of Medical Students, 2021)
Background: The COVID-19 pandemic has been challenging medical professionals and facilities for over a year now. Much of the literature describes pathologic lung changes and complications associated with SARS-CoV-2, with pneumothorax and pneumatoceles not being uncommon. The Case: We describe a case involving a patient that presented to the emergency department with a pneumothorax. Three weeks prior, the patient was hospitalized for 10 days in acute respiratory distress secondary to COVID-19 pneumonitis, which did not require ventilator support. Follow up imaging revealed a 7 cm (AP) x 4.6 cm (transverse) x 2.5 (cc) cm pneumatocele. Conclusion: We speculate that antecedent rupture of an unrecognized pneumatocele likely caused lung collapse leading to the patient’s pneumothorax. This review delves into the etiology of both pneumothoraces and pneumatoceles along with their relation to COVID-19 pneumonia.